2021
DOI: 10.1007/s42489-021-00091-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Augmented Reality Techniques on Cartographic Visualization

Abstract: Augmented reality (AR) is playing an increasingly important role in a variety of everyday application scenarios. Users are not completely disconnected from the current sensory influences of reality. They are merely confronted with additional virtual objects that are projected into reality. This allows users to obtain additional spatial information, which makes this technology interesting for cartographic applications (e.g. navigation). The dynamic positioning of the superimposed image in the scene being viewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Our results follow other authors' findings regarding the positive acceptance of AR and VR by our students [17,32,[63][64][65][73][74][75]. Nevertheless, it is necessary for us to recognize that more coincidences were obtained with results that referred to AR than with those corresponding to VR, where research studies are less abundant, although their number has been growing lately [76].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results follow other authors' findings regarding the positive acceptance of AR and VR by our students [17,32,[63][64][65][73][74][75]. Nevertheless, it is necessary for us to recognize that more coincidences were obtained with results that referred to AR than with those corresponding to VR, where research studies are less abundant, although their number has been growing lately [76].…”
Section: Discussionsupporting
confidence: 89%
“…They demonstrated the influence of the amount of data and the hardware equipment on ensuring a smooth real-time visualization in a VR situation, and concluded that CAD models offer a better performance than mesh models. In the same vein, Dickman et al [17] concluded, but this time with respect to AR, that different techniques influence the visualization and perception of AR elements in 3D space.…”
Section: Introductionmentioning
confidence: 99%
“…The program was an attractive tool for effective public participation (Maksymiuk et al, 2017). 3D visualization techniques have emerged as a new global trend in spatial and urban-architectural planning (Broll et al, 2004;Dickmann et al, 2021;Phan & Choo, 2010).…”
Section: Fig 2 Stereoscopic Visionmentioning
confidence: 99%
“…It refers to augmented forms of representation that enable the integration of different (cartographic) elements into the representation of material spaces. The degree of integration can range from sparse to intensive, from an addition of virtual elements to the integration of complex, even multisensory information [126][127][128][129][130]. Social hybridizations have an effect on the differentiation of commonsense and 'expert special knowledge stocks' regarding to spatial questions.…”
Section: Possibilities Of Reintegrating Aesthetic References By Means...mentioning
confidence: 99%